Akal Perspektif Al-Qur'an - Muh Daming K. (Zawiyah: Jurnal Pemikiran Islam, 2016)
Intelligent is one of capacity among capacity of human in which purpose as tool and pair of scales for knowlegde to understand either right and worng. Intelligent in al-Qur'an can be purposed as medium to think of authorization and creation of Allah SWT. In any circumtances.Intelligent can show affection. Intteligent pepople will learn from saying of Allah SWT., as guidance to the right. If intelligent is safe, morals will be perfect.